2014
DOI: 10.4308/hjb.21.4.180
|View full text |Cite
|
Sign up to set email alerts
|

Hunting at the Abun Regional Marine Protected Areas: A Link Between Wildmeat and Food Security

Abstract: Native Papuans are relied on hunting for subsistence purposes and significantly contributed to traditional cultures. However, in Papua information on hunting is limited and largely restricted to anthropological setting with most observations were done on the forest sites in lowland and highland landscapes. This study focuses on the contribution of hunting on food security along the coastal forests at the Bird's Head Peninsula. Do people live near coastal sites mostly rely on marine resources as protein source?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…2011), but ; et al also confirmed that the practice of hunting was primarily for trade and consumption (Pattiselanno 2006;Pattiselanno & Lubis 2014;Pattiselanno & Mambai 2015 and IDR15,000 (or US$1.13) for pork. The total hunting take was valued at IDR230,625,000 (US$17,435).…”
Section: S Ethodmentioning
confidence: 92%
See 1 more Smart Citation
“…2011), but ; et al also confirmed that the practice of hunting was primarily for trade and consumption (Pattiselanno 2006;Pattiselanno & Lubis 2014;Pattiselanno & Mambai 2015 and IDR15,000 (or US$1.13) for pork. The total hunting take was valued at IDR230,625,000 (US$17,435).…”
Section: S Ethodmentioning
confidence: 92%
“…In this study, we determine the hunting returns from indigenous hunting which will allow us to calculate the harvest rate of hunted species and to predict the ongoing effect of hunting on prey species targeted by hunters. We conducted our studies in lowland coastal forests where indigenous hunting is commonly performed by local communities (Pattiselanno & Lubis 2014;Pattiselanno & Mambai 2015). This study also wishes to measure the impact of hunting on the lowland coastal forests at the Bird's Head Peninsula in West Papua.…”
Section: Et Almentioning
confidence: 99%
“…Usually, to obtain animal protein food source, the local farmers hunt some animals in the forest, resulting in quite high consumption of meat. [28] say that hunting is performed in order to supply a family consumption with complete meals. Deer and wild pig are killed in primary forest.…”
Section: Discussionmentioning
confidence: 99%
“…Hunting for bushmeat has long been a controversial issue due to concerns over the conservation impacts of wildlife depletion but bushmeat hunting is also important in helping rural households to achieve food security (Fa et al, 2009;Nyahongo et al, 2009;Rentsch and Damon, 2013;Golden et al, 2014;Cawthorn and Hoffman, 2015;Reuter et al, 2016;Nielsen et al, 2018). In the Abun region of West Papua, Indonesia, hunting has proved to be an important factor in fighting food insecurity, as wildmeat accounted for 49% of the diets of respondents (Pattiselanno and Lubis, 2014). Bushmeat hunting around the world remains an important source of protein and, more importantly micronutrients, for many rural households and can provide vulnerable populations such as children with important micronutrients (Golden et al, 2011;Van Vliet et al, 2015).…”
Section: Contribution Of Wild Foods To Dietsmentioning
confidence: 99%